Investigation of the temperature impact on the operation of a nonlinear electromagnetic vibration energy harvester - Kulik, Marcin; Gabor, Rafał (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
This paper presents a detailed study of the impact of temperature on the performance of a nonlinear electromagnetic vibration energy harvester, which is applied in autonomous power systems. The variability of material properties under the influence of temperature, such as stiffness, damping, and magnetic induction, significantly affects the operational characteristics of the device. A mathematical model accounting for these factors, including linear and quadratic temperature coefficients, optimized using a genetic algorithm, is presented in the article. The simulation results were compared with experimental data, showing good agreement, particularly in the range of frequency bandwidth and output voltage. It was demonstrated that higher temperatures lead to a reduction in mechanical and magnetic stiffness, resulting in decreased energy conversion efficiency.